The Hornbill as an Inspirational Idea for the Creation of Painting Artworks - Lalang Cakra Buana (Tradition and Modernity of Humanity, 2026)
The hornbill (family Bucerotidae) is one of the most morphologically distinctive and visually compelling bird species inhabiting the tropical forests of the Indonesian archipelago. Characterized by its large curved beak, prominent casque atop its head, striking contrasting plumage, and deeply resonant presence in indigenous cultural traditions, the hornbill presents an exceptionally rich subject for artistic exploration. Beyond its formidable aesthetic appeal, the hornbill holds a position of profound cultural significance in the traditions of the Dayak communities of Kalimantan and the Batak communities of North Sumatra, where it is revered as a guardian spirit, a messenger of ancestral worlds, and a living symbol of ecological equilibrium. Despite the hornbill's exceptional visual and symbolic richness, no prior research-based art creation study has systematically integrated its morphological, cultural, and ecological dimensions within a unified painting practice, a gap this study directly addresses. This research-based art creation study aims to systematically explore the aesthetic, symbolic, ecological, and cultural potential of the hornbill as the central source of inspiration for the creation of contemporary paintings. The methodology employed follows a three-stage research-based art creation model encompassing exploration, experimentation, and realization, drawing on field observation in Sumatran national parks, structured ethnographic interviews with indigenous community elders, and sustained studio practice spanning fourteen months. Three thematic painting series were developed: the naturalistic-expressive series "Guardians of the Forest", the semi-abstract cultural series "Ancestral Spirits", and the critically oriented mixed-media series "A Deferred Extinction". The results demonstrate that the hornbill's morphological distinctiveness, cultural symbolism, and endangered conservation status collectively generate a powerful conceptual framework capable of producing paintings of profound aesthetic depth, ecological relevance, and cultural resonance. The resulting works function simultaneously as autonomous artworks and as instruments of environmental advocacy.